Social processes in relation to the approval and implementation of Goat National Law Nº 26.141/2006: an anthropological approach from the Northeast of San Luis Province (Huellas, 2023)
In 2006, the National Congress passed the Goat Law Nº 26.141, as part of a series of public policies that focused on the rural sector and, specifically, on family farming. The aim of this article is to analyze, from an anthropological perspective, the implementation of the Goat Law Nº 26.141, as a public policy, paying special attention to the diversity of actors and social relations involved in the process of its implementation in the Northeast of San Luis. Fragments of the ethnographic fieldwork carried out between 2019 and 2021 with the Unión de Productores/as Caprinos/as (Union of Goat Producers), an organization in northeastern San Luis, will be used for this study. First, the socio-productive strategies of the rural producers who are part of the organization will be studied. In the second section, the socio-historical context in which the Goat Law was enacted will be reviewed, taking into account the ways in which the agribusiness model was established in the country, and the characteristics adopted by rural development programs since the 1990s. Finally, the dynamics and modes of operation of the Goat Law will be studied in a situated manner.
Keywords: organizational processes; public policies; rural development; participation; associativism